Effect of cold and heat shock treatments on the response of Brucella melitensis to various environmental stresses. Issue 3 (12th September 2016) - Zarei, Mehdi; Pourmahdi Borujeni, Mahdi; Yousefvand, Amin
Abstract: The effect of cold shock (10 °C for 2 h) and heat shock (42 °C for 45 min) treatments on the viability of Brucella melitensis under adverse conditions was investigated. Viability of B. melitensis cells during storage at 4 °C was significantly affected by cold shock and heat shock treatments. While cold‐shocked cells became more resistant to cold storage, a significant decrease in the viable population of heat‐shocked cells was observed. Similarly, cold‐shocked cells of B. melitensis became more resistant and heat‐shocked cells became more susceptible to acidic conditions. Although cold shock treatment did not affect the thermal tolerance of B. melitensis, heat shock treatment increased significantly the thermal tolerance of the bacterium. Nevertheless, these shock treatments, under the conditions tested, did not alter the susceptibility of B. melitensis to incubation at −18 °C and the presence of 10% NaCl. Practical applications: In the food industry, cooling chains and heating processes could potentially induce a cold or heat shock phenomenon. Hence, this information should be taken into account in the development of food preservation measures and for conducting risk assessments on the importance of this pathogen in food processing operations.